Synthesis, Characterization and Theoretical Studies of New Organotellurium Compounds Based on (4-(((1S,E)-1,7,7-trimethylbicyclo[2.2.1]heptan-2-ylidene)amino)phenyl)mercury(II) Chloride - Nuha Hussain Al-Saadawy (Universitas Gadjah Mada, 2021)
The current study aimed to prepare new organomercury and organotellurium compounds based on the condensation reaction of 1,7,7-trimethylbicyclo[2.2.1]heptan-2-one (camphor) and p-aminophenyl mercuric(II) chloride. All the prepared compounds were characterized using different methods such as infrared spectrum, nuclear magnetic resonance, and CHN analysis. The analysis results concurred with the suggested chemical structures of the prepared compounds. Density functional theory has been applied with the basis set 3-21G to investigate the molecular structure of the prepared organotellurium compounds. Geometrical structure, HOMO surfaces, LUMO surfaces, and energy gap have been produced throughout the geometry optimization. The molecular geometry and contours for organotellurium compounds have been investigated throughout the geometrical optimization. Also, the donor and acceptor have been studied by comparing the HOMO energies of the prepared organotellurium compounds. Finally, the electronegativity, electrophilicity, ionization potential, electron affinity, and lower case of organotellurium compounds have been calculated and discussed.